The integrated contribution of surface topology to anti-icing effectiveness. (1st March 2022) - Truong, Mai Xuan; Hanh, Vu Thi Hong; Nguyen, Thanh-Binh
Abstract: The effects of topology parameters at micro-scale on anti-icing performance have not been investigated theoretically and clearly. In this work, we figured out the affection of structure parameters and derived quantities to anti-icing performance in terms of adhesive strength. Well-textured silicon microstructure with different topologies and surface energies was generated via the lithography process. The parameters including pillar height, top diameter, and spacing were simultaneously investigated through the transition energy barrier approach. The results demonstrated the integrated contribution of all parameters in anti-icing performance, instead of independent effects. Furthermore, our results disclosed the correlation contribution of edge and top effects in adhesion strength. This insight should lead to an understanding of icing phenomena and the design of icephobic surfaces.